Determining the main criteria for the development of smart cities based on factor analysis - Kulbaeva, A.A.; Nakhipbekova, S.A.; Ydyrys, S.S.; Kulbaeva, M.A.; Akhmetova, K.I. (BUKETOV BUSINESS REVIEW, 2023)
Object: The aim is to use the Analytical Hierarchy Process (AHP) methodology to examine these requirements for a smart city and assign weight to each element considered important for its development. Methods: Statistical and survey methods are used in the article. The answers to the survey were entered into the SPSS 22 program, and the normative test results and factor analysis were made regarding the variable elements for creating a smart city. Findings: A smart city is a city that includes aspects of its residents’ well-being, quality of life, economic, technological, mobility, and environmental friendliness. In order to achieve the status of “Smart City” there are dimensions to consider. The strategic decisions made by Smart City planners play an important role in determining how a city uses resources and opportunities through the use of modern technologies to create a foundation for environmental, societal-impacting innovation. Smart cities focus on various elements of humanity, education, environment, technological infrastructure, social development and urban growth. Conclusions: Smart environment and smart mobility have been found to be two important factors for the successful construction of a smart city. The real values that form “smart cities” are based on the balance of factors such as “smart” environmental practices, “smart governance”, “smart life”, “smart mobility”, “smart people” and “smart economy”. These key dimensions work together to deploy technologies that help realize the concept of a “smart city”.